Comparative analysis of frameworks for creating user interfaces in iOS Systems - Sebastian Słupny; Edyta Łukasik (Journal of Computer Sciences Institute)
The paper presents a detailed comparative analysis of two key frameworks used for creating user interfaces in iOS: SwiftUI, which is based on a declarative approach, and UIKit with Storyboard, which uses an imperative approach. The aim of this analysis is to assess the impact of each environment on the design process, development, and final quality of mobile applications. For comparison, the RandomPhotos application was created, displaying random photos. The application was developed in two versions: one using SwiftUI and the other using Storyboard and UIKit, allowing for a direct comparison of performance, flexibility, and usability of both frameworks. The thesis "SwiftUI is more efficient during the startup of applications handling a data collection" was confirmed.